Influence of increasing proportion of supplemental nitrogen from urea on intake and fermentation characteristics in beef steers consuming low-quality, tallgrass-prairie forage - Köster, H.H.; Cochran, R.C.; Vanzant, E.S.; Kreikemeier, K.K.; St Jean, G.; Titgemeyer, Evan C.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five ruminally and duodenally fistulated Angus × Hereford steers were used to determine intake and fermentation responses associated with increasing the proportion of supplemental degradable intake protein (DIP) provided by urea. Steers had free access to a dormant, tallgrass-prairie forage. The supplemental DIP was provided by sodium caseinate and (or) urea , at a level that was determined previously to optimize use of a similar forage. Supplemental DIP was balanced with corn starch to provide a final supplement of 40% crude protein. Percentages of DIP from urea were: 0, 25, 50, 75, and 100%. Supplements were given intraruminally. Increasing the percentage of urea as supplemental DIP from urea did not significantly affect forage DM intake; however, fermentation characteristics changed.
Keywords: Beef; Beef cows; Intake; Rumen fermentation; Forage